Acne and Acneiform Eruptions 2017
DOI: 10.5772/65634
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Acneiform Eruptions

Abstract: Acne vulgaris is a chronic skin disease that develops as a result of inlammation of the pilosebaceous unit and its clinical course is accompanied by comedones, papules, pustules, and nodules. A diferent group of disease, which is clinically similar to acne vulgaris but with a diferent etiopathogenesis, is called "acneiform eruptions." In clinical practice, acneiform eruptions are generally the answer of the question "What is it if it is not an acne?" Although there are many subgroups of acneiform eruptions, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…26 The use of systemic corticosteroids is still controversial because of its side effects, such as striae, acneiform eruptions, obesity, cataract, and hypertension. 27 The dose used varies, from an initial 20-40 mg of prednisone per day, tapered down to 5 mg per day within several weeks, to a pulse therapies regime, which is administering short-term high dose oral prednisolone (100-300 mg) or intravenous methylprednisolone (250 mg). 14 Ahu et al used oral steroids and found that 7 (46.7%) of patients showed total recovery, and 5 (33.3%) showed regrowth in the lesion region and positive light pull.…”
Section: Discussionmentioning
confidence: 99%
“…26 The use of systemic corticosteroids is still controversial because of its side effects, such as striae, acneiform eruptions, obesity, cataract, and hypertension. 27 The dose used varies, from an initial 20-40 mg of prednisone per day, tapered down to 5 mg per day within several weeks, to a pulse therapies regime, which is administering short-term high dose oral prednisolone (100-300 mg) or intravenous methylprednisolone (250 mg). 14 Ahu et al used oral steroids and found that 7 (46.7%) of patients showed total recovery, and 5 (33.3%) showed regrowth in the lesion region and positive light pull.…”
Section: Discussionmentioning
confidence: 99%